2021
DOI: 10.4314/as.v20i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of Sesame (Sesamum indicum) as influenced by plant population density and organo-mineral fertilizer rates

Abstract: Sesame (Sesamum indicum L.) is an important oil-seed crop cultivated for its high nutrition and edible seeds. However, its cultivation is affected by low soil fertility, wrong choice of plant population density and time of sowing. The experiment was carried out during the 2016 and 2017 cropping seasons at the Research Site of Agronomy Section, Kabba College of Agriculture, Kabba, Kogi State, Nigeria. The experiment evaluated the influence of plant population density and organo-mineral fertilizer rates on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Specifically, Ogar and Asiegbu (2005) and Nwite et al (2013) reported that manure enhanced the yield of fluted pumpkin. Oloniruha et al (2021) reported a similar trend on sesame. The impressive results in the present study would be partially explained by improvements in soil structure due to cattle dung (Ezenne et al, 2019) and poultry manure (Obalum et al, 2020).…”
Section: Discussionmentioning
confidence: 54%
“…Specifically, Ogar and Asiegbu (2005) and Nwite et al (2013) reported that manure enhanced the yield of fluted pumpkin. Oloniruha et al (2021) reported a similar trend on sesame. The impressive results in the present study would be partially explained by improvements in soil structure due to cattle dung (Ezenne et al, 2019) and poultry manure (Obalum et al, 2020).…”
Section: Discussionmentioning
confidence: 54%
“…But, above all, given soil low initial organic matter and high sand contents, the resulting low biological activity is responsible for the low mineralization observed of the added organic fertilizers. In other works, the best yield performance of Sesame was achieved with 1.5 t ha -1 of organo-mineral fertilizer and thus is recommended for optimum production of this crop (Oloniruha, 2021). Moreover, Hui (2021) and Islam et al (2021) found that biochar and plastic mulches applications in Olericulture had a positive effect on fruit yield.…”
Section: Fruit Yieldsmentioning
confidence: 84%
“…This performance could be ascribed to the capacity of the various soil amendments to supply plants with regular available N in a sustained manner throughout the whole vegetative period. This is an important feature in soils characterized by required N availability, as it lowers the possibility to have N plant deficiencies during important vegetative stages, and decreases the risk of N leaching and N 2 O gas emissions [25,39,16,40]. Similarly, improved nutrient availability positively affected cell physiology that translated into optimum yield through the translocation of photosynthates to the sink (seed), which promoted seed weight.…”
Section: Discussionmentioning
confidence: 99%
“…Population density is an integral factor of yield, and a uniform plants distribution per unit area is a requirement for yield stability [24]. The finding of [25] revealed that Sesame with closest spacing was better in terms of seed yield per land area while widest spacing produced the maximum individual yield attributes. Commercial production of sesame in Ghana is new and is limited to few farmers in northern Ghana.…”
Section: Introductionmentioning
confidence: 99%